How to exploit course books with the help of drama activities - Dömötör Rita (2003)
This thesis focuses on the importance and usefulness of drama activities and expounds how to improve course books and how to motivate children with the help of them. First it explains the concept of drama and divides the drama activities into four major groups. Than it defines the four categories one by one. It also draws the attention towards the importance of drama activities why they are so beneficial and useful. Teacher-student relationship is also mentioned, how to build up a good rapport with the students and how to motivate them properly. Later it is made clear how to implement and evaluate drama activities. Finally it gives great examples and ideas how to make a course book lively and enjoyable for both the students and the teacher.